Open or Delete: Decision-makers’ Attitudes Toward E-mail Marketing Messages - Andersson, Martin; Fredriksson, Martin; Berndt, Adele (Advances in Social Sciences Research Journal, 2014)
Organisations make use of e-mail marketing messages, with Swedish companies spending SEK40 million on this form of marketing communication. The purpose of this paper was to examine the attitudes of decision-makers in the Swedish manufacturing industry regarding e-mail marketing messages received. The authors used a quantitative research approach with an online-survey in order to collect the necessary data. The population was decision-makers within the manufacturing industry in Sweden and 1 777 responses from decision-makers were received and analysed. The majority of decision-makers tend to have negative attitudes toward e-mail marketing messages. Differences in attitudes exist between those of different ages and positions within companies. While respondents indicated that they check their e-mail frequently, no significant differences in attitudes to e-mail marketing messages could be identified. Marketers can attempt to improve attitudes among recipients by building relationships with the recipients prior to sending e-mail marketing messages, and paying attention to the layout and content of the e-mails.